Infectious risks of blood transfusions: Recent advances in testing technologies and new approaches to surveillance and decision‐making. (July 2013) - Busch, M. P.
<x xml:space="preserve">Abstract</x> Introduction Despite impressive progress in reducing risk of established transfusion‐transmitted infectious diseases (TTIDs), new emerging infectious disease (EID) threats continue to be identified and cause pressure to expand deferrals and testing in order to maintain the safety of transfusions. Aims Review recent progress in developing approaches for estimation of residual risk and test efficacy for established TTIDs, as well as new approaches for systematic surveillance and assessment of EIDs that may threaten the blood supply. Methods Summarize recent publications and initiatives of the global blood banking community directed at reducing risk of traditional TTIDs as well as recent responses to EID threats. Results Implementation of enhanced serological assays and nucleic acid amplification technologies (NAT) has virtually eliminated risks of major TTIDs. Formal approaches have recently been developed to monitor and respond to EIDs by examining their properties with respect to transmissibility and potential for causing significant disease in transfusion recipients. New tools for quantitative risk assessment are under development to facilitate rigorous evaluation of scientific evidence, while also formally soliciting and considering public perception and fear and health economic realities. Conclusion These ongoing efforts at refining our risk surveillance, assessment and decision analysis tools, coupled with focused research to quantify risks and evaluate interventions, presage an era of sustained safety and enhanced public trust in the blood supply.